Building Project Success through Transactional Leadership, Training, and Motivation: A Study on the Creative Event Industry: JEL Classification: J16, O33, D83, J22, L26 - Aryani, Irma; Insan, A. Nur; Sawaji, Jamaluddin; Dwiyanti, Andi Amytia Resty (Newinera Publisher, 2025)
This study explores how transactional leadership, short term training, motivation, and job satisfaction influence project success within the event and wedding organizer industry in Makassar, a sector characterized by temporary teams and heavy reliance on freelance workers. Using a quantitative survey approach, data were gathered from 134 freelancers selected through purposive sampling. Multiple linear regression was applied to examine both the individual and simultaneous effects of the four predictors. The results show that all variables significantly and positively contribute to project success, with transactional leadership standing out as the strongest determinant, followed by job satisfaction, motivation, and short yet targeted training. These findings reveal that successful event projects depend not only on technical execution but also on the clarity of leadership, the relevance of preparatory training, and the psychological engagement of freelance workers. The study highlights that even in fast paced and short term project environments, clear guidance and structured supervision help freelancers orient themselves quickly toward task demands. Focused training enhances readiness and reduces errors, while motivation and job satisfaction strengthen commitment and foster smoother collaboration. Together, these elements form a human resource framework that supports consistent and reliable project performance. The results contribute to the growing understanding of HR management in gig based work structures and underscore the importance of designing adaptive leadership and training practices that align with freelance realities. The study also offers practical implications for event managers seeking to improve project outcomes and suggests that future research may benefit from exploring additional variables such as organizational culture and team communication.